Effects of implementation of an urgent surgical care service on subspecialty general surgery training - Wood, Leanne (Canadian Medical Association, 2010)
BACKGROUND: In July 2007, a large Canadian teaching hospital realigned its general surgery services into elective general surgery subspecialty-based services (SUBS) and a new urgent surgical care (USC) service (also know in the literature as an acute care surgery service). The residents on SUBS had their number of on-call days reduced to enable them to focus on activities related to SUBS. Our aim was to examine the effect of the creation of the USC service on the educational experiences of SUBS residents. METHODS: We enrolled residents who were on SUBS for the 6 months before and after the introduction of the USC service. We collected data by use of a survey, WEB eVAL and recorded attendance at academic half days. Our 2 primary outcomes were residents’ attendance at ambulatory clinics and compliance with the reduction in the number of on-call days. Our secondary outcomes included residents’ time for independent study, attendance at academic half days, operative experience, attendance at multidisciplinary rounds and overall satisfaction with SUBS. RESULTS: Residents on SUBS had a decrease in the mean number of on-call days per resident per month from 6.28 to 1.84 (p = 0.006), an increase in mean attendance at academic half days from 65% to 87% (p = 0.028), at multidisciplinary rounds (p = 0.002) and at ambulatory clinics and an increase in independent reading time (p = 0.015), and they reported an improvement in their work environment. There was no change in the amount of time residents spent in the operating room or in their overall satisfaction with SUBS. CONCLUSION: Residents’ education in the SUBS structure was positively affected by the creation of a USC service. Compliance with the readjustment of on-call duties was high and was identified as the single most significant factor in enabling residents to take full advantage of the unique educational opportunities available only while on SUBS.